Pelaku Bullying Ditinjau Dari Perspektif Teori Identitas Sosial Sebuah Systematic Review Literature - Sakroni, Sakroni; Subardhini, Meiti; Riyadi, Sabar (Santhet (Jurnal Sejarah Pendidikan Dan Humaniora), 2024)
This study investigates bullying behavior from the perspective of social identity theory. Bullying is a serious issue affecting the well-being of individuals in schools and communities. The primary aim of this research is to explore how identification with specific social groups influences bullying behavior. The methodology employed is a systematic literature review focusing on inclusion criteria related to social identification, group dynamics, status and power, and contextual factors. Key findings indicate that social identification plays a pivotal role in bullying behavior, while group dynamics, social status, and influences from school, family, and social media contexts are also significant. The research findings carry significant implications for enhancing anti-bullying efforts, primarily by focusing on the development of more impactful interventions. It is vital to prioritize the creation of safe and inclusive school environments as a key aspect in combating bullying effectively.